Place of Plasma Argon Coagulation in the Treatment of Vascular Abnormalities of the Digestive Tract in Adults - Samir Mrabti; Ahlame Benhamdane; Asmae Sair; Tarik Addajou; Réda Berrida; Sara Sentissi; Ilham Koti; Fedoua Rouibaa; Ahmed Benkirane; Hassan Seddik (Journal of Coloproctology, 2023)
The aim of our study is to evaluate the value of Argon Plasma Coagulation in the treatment of gastrointestinal vascular abnormalities.